Hubungan Beban Kerja Dengan Tingkat Stres Perawat Ruang Intensive Care Unit dan Instalasi Gawat Darurat - Nonik Eka Martyastuti; Isrofah Isrofah; Khalilatun Janah (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2019)
The workload in the room is not always a cause of stress on nurses, the workload will be a source of stress if the number of workloads is not proportional to the ability of both the physical or expertise and the time available to nurses. Besides, nurses are faced with patients who trigger an increasing stress on nurses. This research was conducted at Siaga Medika General Hospital in Pemalang. The research design used quantitative associative analytic through cross-sectional approach. The sample of this study was 45 nurses who served in the Intensive Care Unit and Emergency Departments because the nurses' stress levels were higher than the nurses’ stress levels in the other treatment rooms (ward) obtained through total sampling because the population was less than 100, so that all population used as research samples. The Work Stress research instrument used the standard Depression Anxiety Stress Scale questionnaire, while the workload questionnaire adopted the previous research and was modified. The results showed that there was a correlation between workload and stress level of Intensive Care Unit nurses and stress of Emergency Departments nurses. This showed that nurses who have a heavy workload that is not comparable to the duties of nurses with the average number of patients, the number of types of work that must be done. If this is not managed properly, it will cause increased stress.H This is what becomes the workload of Intensive Care Unit and Emergency Departments nurses in Siaga Medika General Hospital in Pemalang which can cause an increase of stress.